Big Five Personality As Moderating The Effect Of Islamic Financial Planning - Aryandhana Mulyana Haris, Dea; Taufiq Possumah, Bayu; Abdul Fatah, Dede (International Journal of Educational Research & Social Sciences, 2021)
Islamic financial planning is a making process of financial planning in prudence to make it compatible with Islamic law in order to achieve the level of Al-Falah, that is the blessing of dunya and the salvation of akhira. Yet, with the importance of Islamic financial planning, the individuals who apply the Islamic financial planning in managing their wealth are still rare. So that this research intends to discover the influence of Islamic financial literacy towards each individual’s Islamic financial planning, and moderation effects given by the big five personality trait. The researcher used the simple regression test to find out the Islamic financial literacy effects towards the Islamic financial planning, and used the analysis of moderated multiple regression (MMR) to take the idea that the big five personality trait can moderate the Islamic financial literacy effects towards the Islamic financial planning. The data is collected by using the survey technique through questionnaire distribution to 115 moslem entrepreneurs in Bandung area. The result of this research shows that the Islamic financial literacy influences the Islamic financial planning significantly, and the big five personality trait partially moderates that influence. Furthermore, the conscientiousness and opennes to experience personality trait moderate the influence of Islamic financial literacy towards Islamic financial planning, while the other three of big five personality trait do not moderate.